2020
DOI: 10.3390/nu12092617
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Dietary Supplementation on Aggressive Behaviour in Australian Adult Male Prisoners: A Feasibility and Pilot Study for a Randomised, Double Blind Placebo Controlled Trial

Abstract: This study aimed to assess the feasibility of conducting a nutrition trial in adult male prisoners. Adult male prisoners were recruited for a 16-week randomised control trial comparing the effect of ingestion of omega-3 long chain polyunsaturated fatty acids (n-3 LCPUFA) and multivitamin supplements versus placebo on aggressive behaviour. The baseline and post-intervention assessments from the participant blood samples were the erythrocyte n-3 LCPUFA levels as well as measures of aggressive behaviour determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 32 publications
(50 reference statements)
0
9
0
Order By: Relevance
“…Our feasibility study showed that prisoners are 4.3 times more likely to have an IBOS of > 2, if they are below the cutoff of 6% omega-3 index [ 38 ] but this does not show causality. This multi-centre trial is adequately powered to demonstrate the effect of n-3 LCPUFA on aggressive behaviour in adult male prisoners.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our feasibility study showed that prisoners are 4.3 times more likely to have an IBOS of > 2, if they are below the cutoff of 6% omega-3 index [ 38 ] but this does not show causality. This multi-centre trial is adequately powered to demonstrate the effect of n-3 LCPUFA on aggressive behaviour in adult male prisoners.…”
Section: Discussionmentioning
confidence: 99%
“…Based on our successful model from the feasibility study [ 38 ], one Correctional Centre Officer per site will be seconded to the research project and they will take on the role of trial coordinator, referred to as Project Officers. Project Officers will be trained at the University of Wollongong prior to the commencement of the trial.…”
Section: Methods: Participants Interventions and Outcomesmentioning
confidence: 99%
See 2 more Smart Citations
“…Two additional studies found aggression‐reducing effects of omega‐3s in prison populations. One exception was an Australian prison study that showed null results (Cortie et al., 2020). In another study, 221 Dutch prisoners received either a dietary supplement that contained omega‐3s and vitamins and minerals or a placebo (Zaalberg et al., 2010).…”
Section: Part Ii: Breaking the Cycle Of Punishment And Violence Via Nmentioning
confidence: 99%